RETHINKING QADHA DAN QADAR ALLAH: IKHTIAR HIDUP DALAM KETERATURAN MENGHADAPI ERA DIGITAL - Muhammad, Fatar Faqih (IAIN Palangka Raya, 2023)
Humans understand the concept of qadha and qadar resulting in two views, namely: all provisions have been arranged by Allah without needing to make any effort and the view that humans are obliged to make maximum efforts and then accept His destiny. In the digital era, this concept needs to be rethought which has relevance and is more adaptive. The aim of this article is to explain the concept of Qadha and Qadar Allah and their relevance to the digital era, as well as how to live in order in the face of digitalization. This research uses qualitative methods with library research techniques. However, under certain conditions, God's will remains the answer that cannot be achieved even with the most sophisticated technology. The existence of Allah's will should not be used as an excuse for a Muslim not to try and adapt to current developments, including in the digital era. Because the concept of qadha and qadar is actually relevant to the digital era. However, they must be able to combine the two by trying as hard as possible, then surrendering their efforts to God's will. This is what is meant by an effort to live in order in the digital era. A Muslim will not feel alone after struggling and making the most of digital developments. They will find a balance between maximum effort, prayers offered, and submission to Allah's will.